Peningkatan Kemampuan Visual Spasial Melalui Media Pipe Cleaner Pada Anak Usia 4-5 Tahun di RA Dzikrurrahman Karawang - Aisyah, Dewi Siti; Afifah, Alya Nur; Putri, Feronica Eka (Peneliti.net, 2024)
The purpose of this study is to explain the methods and results of learning carried out through pipe cleaner media to improve children's visual-spatial abilities. This research was conducted at RA Dzikrurrahman Karawang in August 2023. The subjects of this study were group A students with a total of 10 children, consisting of 5 boys and 5 girls. This study uses a classroom action research method that refers to Kemmis and Mc Taggart, whose process consists of: a) planning, b) action, c) observation, and d) reflection. This research was conducted in two cycles, the first cycle consisted of 5 meetings, and the second cycle consisted of 3 meetings. Data collection techniques used are tests, observations, interviews, and documentation. Data analysis techniques used are quantitative and qualitative. Quantitative data analysis is to see the percentage of success, while qualitative analysis is to explain the results of the research. The results of this study prove that there is an increase in children after using pipe cleaning media. The results of the pre-action percentage were 31%, the first cycle was 67% and the second cycle was 87%. Pipe cleaning media affects the spatial visual abilities of children aged 4-5 years.